FITOREMEDIASI LIMBAH DOMESTIK (Greywater) MENGGUNAKAN TANAMAN MELATI AIR (Echinodorus palaefolius) DAN ECENG GONDOK (Eichornia crassipes) UNTUK MENURUNKAN KONSENTRASI BOD, COD DAN AMONIA - Nurhidayanti, Nisa; Huda, Helbi Nurul; Ardiatma, Dodit (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 16 No 2 (2022)DO - 10.24843/EJES.2022.v16.i02.p03, 2022)
Sustainable development can lead to an increase in the amount of wastewater produced from industrial waste and household domestic wastewater which contains materials/substances that can endanger human life and disrupt environmental sustainability. The aim of this research is to determine the optimum concentration of domestic wastewater for growth of water jasmine and water hyacinth and to determine the effectiveness of the phytoremediation method using plants water jasmine ( Echinodorus palaefolius ) and  water hyacinth ( Eichornia crassipes ) in reducing  concentrations of BOD, COD and ammonia in domestic greywater wastewater. The stages of the research method began with sampling  waste water, testing wastewater,  acclimatization of plants,  range finding test / phytoreactor test and continued with data analysis. The results of the test parameters of domestic greywater waste for 7 days obtained the final value of COD is 0.50 mg/L, BOD is 0 mg/L, and Ammonia is 0 mg/L. Based on the research results obtained the effectiveness of reducing COD concentrations by 99.65%; BOD of 100%; and 100% ammonia. This shows that the use of the phytoremediation method using water jasmine and water hyacinth is very effective in reducing the levels of BOD, COD and ammonia in domestic greywater wastewater and has met the quality standards for domestic wastewater. Keywords: Phytoremediation, Domestic Greywater, Water Jasmine, Water Hyacinth